2015
DOI: 10.1007/s40266-015-0282-9
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy and Adherence Issues in Treating Elderly Patients with Glaucoma

Abstract: Glaucoma is a leading cause of visual morbidity throughout the world and is an age-related condition, the prevalence of which rises significantly with increasing age. Glaucoma, a condition affecting the optic nerve, has a variety of subtypes with multiple aetiological factors, the most important of which are intraocular pressure (IOP) and increasing age. Treatment by lowering of IOP is the only current method, for which there is evidence, by which the rate of progressive visual deterioration can be slowed or h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 131 publications
(122 reference statements)
0
16
0
4
Order By: Relevance
“…In an overseas clinical study, patients can better adhered with xed-combination therapies than with un xed-combination therapies. 15 Considering that good adherence to therapies is critical for controlling glaucoma progression, 9,36,37 we believe that a xedcombination therapy is an advantageous option for glaucoma treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In an overseas clinical study, patients can better adhered with xed-combination therapies than with un xed-combination therapies. 15 Considering that good adherence to therapies is critical for controlling glaucoma progression, 9,36,37 we believe that a xedcombination therapy is an advantageous option for glaucoma treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A reason for the lack of IOP control in this study may be a lack of adherence to the pharmacotherapy, as most of the patients reported eye irritation from the eye drops during the beginning of treatment in the medical records. In addition, several studies have reported that some patients who are diagnosed with glaucoma do not respond to first-line treatment drugs, and two or more antihypertensive drugs are required to achieve the target IOP (Cheng et al, 2012;Broadway and Cate, 2015;Kass, et al, 2002). When analyzing the final IOP of the patients from Region 3, age was observed to be a risk factor for increased IOP.…”
Section: Discussionmentioning
confidence: 99%
“…Meðferðarheldni raeðst af mörgum þáttum, svo sem fjölda lyfja, aukaverkunum og kostnaði, en einnig af því að gláka getur verið einkennalaus. 8,9 Hafa verður í huga að fjöllyfjameðferð, sjúkdómsbyrði einstaklings og faerniskerðing getur gert sjúklingum erfitt fyrir að koma dropanum í augað, sérstaklega þar sem margir hverjir hafa misst sjónina til að leysa það verkefni af hendi með góðum árangri. 8,9 Mikilvaegt er að raeða þessi atriði við einstaklinga sem nota augndropa að staðaldri og meta hvort þörf sé á ráðgjöf og aðstoð.…”
Section: Umraeðaunclassified
“…8,9 Hafa verður í huga að fjöllyfjameðferð, sjúkdómsbyrði einstaklings og faerniskerðing getur gert sjúklingum erfitt fyrir að koma dropanum í augað, sérstaklega þar sem margir hverjir hafa misst sjónina til að leysa það verkefni af hendi með góðum árangri. 8,9 Mikilvaegt er að raeða þessi atriði við einstaklinga sem nota augndropa að staðaldri og meta hvort þörf sé á ráðgjöf og aðstoð. Mikilvaegt er að heilbrigðisstarfsfólk hafi í huga að augndropar eru lyf sem geta haft margvíslegar líkamlegar aukaverkanir þrátt fyrir að lyfin séu aðeins gefin staðbundið í augu.…”
Section: Umraeðaunclassified
See 1 more Smart Citation